Peran Inovasi Produk Dan Jaringan Bisnis Pada Perkembangan Usaha: Studi Pada Pembuatan Acy Family - Resya Dwi Marselina; Riyan Ismayadi; Bagas Syabani Sabrawera; Ajeng Reni Razmayanti; Yumita Sari Dianti (Institut Nalanda, 2024)
This research was conducted to find out how the role of product innovation and business networks in the development of the Acy Family business. Observation and interviews were the data collection techniques used in this study. The analysis method used is a descriptive qualitative analysis method, namely by collecting, processing and presenting data obtained when conducting research so that complete information is obtained about what is researched. Based on the results of the analysis that has been done, it can be concluded that product innovation and business networks play a very important role in the development of a business. Acy Family uses product innovation and business networks as tools to support its business development. With product innovation and an extensive business network, it will expand the market share of the business so that business income will increase which will have a good impact on the development of a business.